Quantum memories for single photons from cavity-QED - Kuhn, A; Nisbet, P; Dilley, J; Langfahl-Klabes, G; Himsworth, M (2011)
We investigate the feasibility of implementing an elementary building block for quantum information processing. The combination of a deterministic single photon source based on vacuum stimulated adiabatic rapid passage [1,2], and a quantum memory based on electromagnetically induced transparency in atomic vapour is outlined [3]. Both systems are able to produce and process temporally shaped wavepackets which provides a way to maintain the indistinguish ability of retrieved and original photons. We also propose an efficient and robust repeat-until-success quantum computation scheme based on this hybrid architecture. © 2011 IEEE.